SPARTE Study: Normalization of Arterial Stiffness and Cardiovascular Events in Patients With Hypertension at Medium to Very High Risk. Issue 4 (30th August 2021) - Laurent, Stephane; Chatellier, Gilles; Azizi, Michel; Calvet, David; Choukroun, Gabriel; Danchin, Nicolas; Delsart, Pascal; Girerd, Xavier; Gosse, Philippe; Khettab, Hakim; London, Gerard; Mourad, Jean-Jacques; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : The SPARTE study (Strategy for Preventing cardiovascular and renal events based on ARTErial stiffness; URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02617238) is a multicenter open-label randomized controlled trial with blinded end point evaluation, undertaken at 25 French research centers in university hospitals. Patients with primary hypertension were randomly assigned (1:1) to a therapeutic strategy targeting the normalization of carotid-femoral pulse wave velocity (PWV) measured every 6 months (PWV group, n=264) versus a classical therapeutic strategy only implementing the European Guidelines for Hypertension Treatment (conventional group, n=272). In the PWV group, the therapeutic strategy used preferably a combination of ACE (angiotensin-converting enzyme) inhibitor or angiotensin receptor blocker and calcium channel blockers, as well as maximal recommended doses of ACE inhibitors and angiotensin receptor blockers. The primary outcome was a combined end point including particularly stroke and coronary events. Secondary outcomes included the time-course changes in brachial office blood pressure (BP), ambulatory BP, PWV, and treatments. After a median follow-up of 48.3 months, there was no significant between-group difference in primary outcome (hazard ratio, 0.74 [95% CI, 0.40–1.38], P =0.35). In the PWV group, combinations of renin-angiotensin-system blockers and calcium channel blockers were prescribed at higher dosage ( P =0.028), office and ambulatory systolic blood pressure and diastolic blood pressure decreased more ( P <0.001 and P <0.01, respectively), and PWV increased less ( P =0.0003) than in the conventional group. The SPARTE study lacked sufficient statistical power to demonstrate its primary outcome. However, it demonstrated that a PWV-driven treatment for hypertension enables to further reduce office and ambulatory systolic blood pressure and diastolic blood pressure and prevent vascular aging in patients with hypertension at medium-to-very-high risk, compared with strict application of guidelines.